Necesidad de incluir en el art. 33 del código orgánico integral penal el medio empleado para repeler la agresión en la legítima defensa - Tanguila Noteno, Jenny Judith (2017)
Article 33 of the Code of Criminal Integral indicates that there is self-defense, when the person acts in defense of any right, own or someone else, as long as requirements concur: 1. Current and illegitimate aggression; 2. Need for rational defense; 3. Lack of sufficient provocation by who acts in defense of the right. As for the requirement of "rational need for the defense" it is a key aspect assumes offended, since proportionally must match the defensive and aggressive action. In the previous Penal Code means less harmful "rational necessity of the means employed to prevent or repel", ie, that the defender to cover its legitimacy should be used in his defense, you have on hand, question stated as determined in the new penal comprehensive legislation touches the prosecutor and judges, equating the environmental consequences of using employer to prevent or repel, which contains a subjective element that generates risks in its interpretation and application. It is noteworthy that in the rationality of defense, attacks human or instrumental reaction, should not exceed the appearance attacked, so it is necessary to include the means used to repel aggression in self-defense, allowing cede space to subjectivity prosecutors and judges, objectivity according to the absolute rule of law against the unjust act that disturbs social order by affecting an individual or collective interest that deserves legal protection, in which case the rational necessity of the means of defense, it is intertwined with the proportionality itself and to not be illogical has to be rational and this requires something or a means which can make an objective assessment, likely to be understood by everyone not only by the creator of the standard legal. The rationality of the means used to counteract or repel aggression, is based on the proporciona¬lidad of the response is used to effect a suitable or appropriate means, because the hands of one person may not be sufficient to exercise self-defense, fren¬te another subject that pron¬to practice martial arts or self-defense, or who has in his hands a suitable instrument such as a stick or stone ejem¬plo to repel aggression, since the "rational need for defense "is associated with the ra¬zón same and it depends to the level and cul¬tural environment they live or have lived a person is implied the" power of pen-sar, the act of discoursing the understanding ", particularly that ultimately it is difficult to demand who is at a current aggression, which pre-mind discerns on ido¬neidad or rationality of his defense, without a rational means to give an appropriate response to aggression which it is vícti¬ma, because that creates an uncertainty regarding the depen¬de and rationality of the means at its disposal or depends on the intrinsic perception of the response to aggression and, on that basis that a person can act coherently or reflection for not overreach and not incur excesses that generate criminal liability. Accordingly, it is re¬comienda that Article 33 of the Code of Criminal Integral, the second requirement is reformed, including the means used to repel aggression, and to legitimize their defense defender, damaging at least have in hand, thereby ensuring legal certainty, since the rules must be prior, clear, public and apply to the competent authority within this corresponden¬cia way with other legislation, they accept as necessary the use of a me¬dio to exercise self-defense, without free will escape the rationality of a defense.